CYP3A5 and POR gene polymorphisms as predictors of infection and graft rejection in post-liver transplant patients treated with tacrolimus - a cohort study - Ono S; Graziella D’ Agostino Ribeiro Naldi; A. Minari; Thales Pereira; Victor Fossaluza; Nicholas Wagner Eugenio; Marcelo Alves Ferreira; Guilherme Gregório; Lucas Souto Nacif; Luiz D Albuquerque; Ricardo di Lazzaro Filho; Eduardo Luiz Rachid Cançado; et al. (2023)
Abstract Liver transplantation is the only curative option for patients with advanced stages of liver disease, with tacrolimus used as the immunosuppressive drug of choice. However, due to its narrow therapeutic index and high inter- and intra-individual variability, serum monitoring should be frequent. An individual's genetic variability can interfere with drug response, potentially leading an individual to overexposure or underexposure of a drug. This study aims to investigate the association of polymorphisms with infection, acute rejection, and renal failure. This is an observational, prospective, cohort, single-center study in liver transplant patients. Were collected 97 recipients and 97 donors. The logistic regression model found an influence of patients expressing CYP3A5*3 (rs776746) and expressing POR*28 (rs1057868) on the development of acute rejection after liver transplantation (p = 0.028). It also found an association between carriers of the variant allele of the POR*28 gene and infection (p = 0.006 isolated analysis and p = 0.003 combined analysis).